Psychological Dimensions of Family Resilience in Indonesian Single-Parent Families: A Literature Review - Hafshah Najma Qonita; Mira Aryani; Anna Armeini Rangkuti; Zarina Akbar (International Conference on Psychology and Education (ICPE), 2025)
The increasing prevalence of single-parent families in Indonesia, as a consequence of the high rate of divorce or death of a partner, drives the urgency to understand family resilience in this context. This phenomenon is crucial considering that changes in family structure can significantly affect the psychological well-being of both parents and children. This study synthesizes and analyzes the existing literature on the resilience of single-parent families in Indonesia, with a particular focus on the psychological factors influencing family welfare and adaptation. The approach used was a literature review, with articles collected from the Scopus and Google Scholar databases. The initial search process resulted in 1678 articles, which were then filtered down to 20 relevant articles. Key findings suggest that individual psychological factors, diverse coping strategies, and sociocultural support, including the role of gender-based social stigma and religious values significantly affect single-parent family resilience. This study emphasizes the importance of a holistic approach that considers the peculiarities of Indonesia's cultural context in an effort to support the resilience of single-parent families. It is hoped that this research can provide essential insights for the development of social policies and interventions that are more effective for single-parent families in Indonesia.